(untitled) (Proceedings of the International Conference of Community Health and Medical Sciences, 2024)
Diabetes Mellitus sufferers who do not perform with routine control completely will increased the risk of complications and premature death. Education, knowledge, and family support can have an influence in undergoing treatment adherence. The purpose of the study was to analyzed the correlation of education, knowledge, and family support with compliance performing routine control of patients with type 2 DM. This is an observational analytic study with a cross sectional approach using consecutive sampling method. A total of 75 patients with type 2 diabetes mellitus eho are receiving treatment at the Kaliori Health Center were performed for the study. The data was obtained from interviews with patients of type 2 diabetes mellitus education, knowledge, and family support. Data analysis was performed using Fisher’s Exact. The results showed that there was no correlation between the level of education and knowledge with compliance performing routine control of patients with type 2 DM at the Kaliori Health Center (p=0.631, p=0.696), and there was a correlation between family support with compliance performing routine control of patients with type 2 DM at the Kaliori Health Center (p=0.000). The level of education and knowledge will affect therapy adherence because patients would be able to prevent or treat the disease. Good family support can support patients in growing confidence in their ability to perform self-care. In addition, good family support can also increase and foster a comfort and secure feeling, in order to comply the routine controls.